RELASI GENDER PADA RUMAH TANGGA PETANI CENGKEH - Ratmayani Ratmayani; Rahmadanih Rahmadanih; Darmawan Salman (Hasanuddin University, 2018)
Abstract This study aims to (1) identify the pattern of gender relations in the structure of work allocation and the allocation of time on clove farming, (2) to analyze the association between gender relations with revenue allocation on men and women in clove farming. This research was conducted in June 2016, with 34 respondents who are located in Seppong Village, District of Tammero'do, Majene. The method used is quantitative descriptive analysis and chi-square test. This study shows that gender relations in work allocation of clove farming are dominated by male at 50% of activity weeding, replanting, fertilizing, harvesting and transporting the ladder manufacture crop yields; the domination of female at 20% of activities, such as sorting and drying; men and women are equal to 30% of activities like watering, harvesting and sales. Gender relations in the farming clove time allocation dominated by male at 60% of activities such as weeding, replanting, watering, harvesting staircase manufacture, harvesting and transporting the crop; the domination of female at 20% of activities, such as sorting and drying; men and women are equal at 20% at sales activities, and fertilization. There was no association between gender relations with the allocation of income.Keywords: gender relations; male; female; clove farming.